An infantile alantoaxial dislocation with patent foramen ovale managed with titanium cabling and allogenic bone grafts - Seidu A. Richard; Zhi Gang Lan; Xiao Yang; Siqing Huang (MDPI AG, 2018)
Atlantoaxial dislocation is a disorder that is characterized with loss of stability of the atlas and axis (C1-C2) with consequential loss of usual articulation. Although this condition is very common, no one has reported a case as young as our patients. We present a 7-month infant with bilateral paralysis of the lower limbs for four (4) months with no history of trauma. Computer tomographic (CT-scan) imaging revealed alantoaxial dislocation with severe cervical spinal cord compression. The odontoid process is displaced outwardly with no bone destruction. Doppler echocardiogram done revealed patent foramen ovale. Thorough physical examination as well as radiological evaluation revealed no feather malformations. Electrophysio - logical studies reveal normal compound muscle action potentials (CMAP) and sensory nerve action potentials (SNAPs) in all the limbs. Electromyography (EMG) also revealed normal nerves in the limbs and the trunk. We attained a stable fusion and anatomical reduction using a posterior titanium wire and an iliac bone graft harvested from his mother. This is the youngest patient reported in literature. Infantile alantoaxial dislocation should be managed at early stage to prevent long-term neurologic disorders.